Прогноз обсягів упровадження сучасних енергозберігаючих технологій очисних робіт у вугільних шахтах - Makarov V.M.; Perov M.O. (General Energy Institute of the National Academy of Sciences of Ukraine, 2010)
Domestic coal production is carried out with an unfavourable structure of the mine fund, is dominated by companies with limited production capacity due to bottlenecks in the technological chains, as well as the development of complex conditions, which do not always able to effectively apply a high-performance equipment. The situation is aggravated by the acute shortage of working capital for the technical re-equipment and replacement of worn abatement, excavating, transportation and stationary equipment.Output of the coal industry from the crisis could be achieved by increasing the production volumes as a result of effective implementation of mechanized systems, ie, a significant increase in load on the face using the technique of a new technological level.As a result of technical re-equipment of mines can be expected to increase coal production by 20 - 30 million tons, reducing the number of production faces a 30 – 40%, reducing the unit cost of electric energy mine sites in the 1,3 - 1,6 times, resulting in a saving of material, energy, labor. The cost of investments for technical re-equipment of mines are estimated at 7 - 13 billion UAH year.Also due to the choice of optimal treatment of the complexes will improve the quality of coal mined, in particular the fall ash.